Agricultural and forest products as supplementary feeding for tambaqui in polyculture with jaraqui - Guimarães, Sérgio Fonseca; Storti Filho, Atilio (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this paper was to evaluate the performance of tambaqui (Colossoma macropomum) in a polyculture trial with jaraqui (Semaprochilodus insignis), using agricultural and forest products as supplementary feeding for tambaqui. Two ponds, measuring 644 m2 (Pond A, associated with pigs) and 1,075 m2 (Pond B, non associated), were stocked with 0.5 tambaqui/m2 and 0.1 jaraqui/m2. After 371 days, tambaqui showed a mean growth from 18.6±4.5 g to 997.±195.08 g in Pond A, and from 81.4±18.8 g to 519.9±191.7 g in Pond B. Feeding management of Pond A may be a sustainable alternative of tambaqui production in substitution to commercial rations.
Produtos agrícolas e florestais como alimento suplementar de tambaqui em policultivo com jaraqui
Keywords: Colossoma Macropomum; Colossoma Marcopomum; Semaprochilodus; Sus Scrofa